Computational studies on the formation of aza‐oxypentadienyl intermediates from alkylidene oxaziridines and keteneimine oxides and their conversion to 1, 5‐dihydropyrrolones. Issue 4 (26th September 2018) - Villar, Pedro; Guillade, Lucía; González‐Pérez, Adán B.; de Lera, Angel R.
Abstract: The rearrangements of alkylidene oxaziridines1a, b (a, R = Me;b, R = OMe) and keteneimine oxides1'a, b to 1, 5‐dihydropyrrolones3a, b have been computationally studied at the UM062X/Def2TZVPP(PCM, TFE)//UM062X/Def2SVP(PCM, TFE) level. The mechanism for conversion of1a ‐3a is predicted to be stepwise, with intermediacy of the acyclic aza‐oxypentadienyl species4a . The stabilization provided by the nitrogen of the oxaziridine makes the ring opening of1a to diradical/zwitterionic intermediates4a more feasible than in the case of the vinyl allene oxide counterparts. The formation of aziridinone2a from1a showed competing activation energies but2a was found to be a thermodynamically less stable species than3a . When the Me group at N is exchanged by the electron‐donating OMe substituent in1b, the diradical species and the corresponding transition structures are more stabilized and therefore the aziridinones are not required as intermediates in the conversion of1b to3b . Keteneimine oxide1′ is predicted to directly generate diradical4 by C‐O ring opening although through a less favored transition state. Abstract : Computational studies on the mechanism for conversion of highly unsaturated keteneimine oxides and alkylidene oxazirines to 1, 5‐dihydropyrrolones is predicted to be stepwise, with intermediacy of the acyclic aza‐oxypentadienyl diradical/zwitterionic species.